Identification of Salmonella in Beef at Binjai City Market - Rahmad Hidayat Nasution; Nur Asmaq; Purwo Siswoyo (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Beef is one of the most important sources of animal protein with high nutritional value. This study aimed to identify the presence of Salmonella bacteria in beef sold at Pasar Tavip Binjai and Pasar Kebun Lada, Binjai City. The research was conducted using laboratory testing methods at the Medan Veterinary Center Laboratory during October–November 2025. A total of 13 beef samples were collected through random sampling, consisting of 10 samples from Pasar Tavip Binjai and 3 samples from Pasar Kebun Lada. Each 100-gram sample was placed in a sterile plastic bag, transported using a coolbox with ice packs, and analyzed through pre-enrichment in 225 ml Lactose Broth (LB) for 24 hours at 37°C, enrichment with Tetrathionate Broth (TTB) and Rappaport Vassiliadis Broth (RV), isolation on Hektoen Enteric Agar (HE), Xylose Lysine Deoxycholate Agar (XLD), and Bismuth Sulfite Agar (BSA), and biochemical confirmation using Triple Sugar Iron Agar (TSIA), Urease, and Lysine Decarboxylase Broth (LDB) in accordance with the National Standardization Agency standards (2008). The test results showed that all samples were negative for Salmonella (100%). No specific Salmonella colonies were found on the selective media, and no positive reactions occurred in the biochemical tests. These results indicated that the beef in both traditional markets was free from Salmonella contamination during the sampling period.